PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Juni Maryam Hasibuan; Mukmin Saipul Daulay; Nurhalimah Harahap; Era Mutiah (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2025)
Learning motivation is a crucial factor in determining the effectiveness of the learning process in primary education. However, low student learning motivation remains a common issue in classroom practice. One strategy that teachers can employ to enhance students’ learning motivation is the provision of rewards as a form of positive reinforcement. This study aims to examine the effect of reward provision on the learning motivation of fifth-grade students at SD Negeri 1104 Sipagabu. This research employed a quantitative approach with a simple correlational design. The participants consisted of all fifth-grade students, totaling 31 students. Data were collected using reward and learning motivation questionnaires and analyzed through simple linear regression, t-test, and coefficient of determination analysis. Based on the results of the t test, it was obtained that t count = 1.95 with a significance level of 0.05 with degrees of freedom df (n-2) = 31-2 = 29, so that t table = 1.699 was obtained. The calculation results obtained t count > t table, namely 1.95 > 1.699. From the test criteria above, H0 is rejected or Ha is accepted, meaning that there is a significant influence on the provision of rewards on the learning motivation of class V students of SD Negeri 1104 Sipagabu, Aek Nabara Barumun District, Padang Lawas Regency. Then in the determination test the R square value is 0.7568 or 75.68%, meaning that giving rewards can contribute to increasing student learning motivation and the rest is explained by other variables of 24.32%.